Effectiveness of teach-back health education combined with Photo Therapy in colorectal cancer patients with permanent enterostomy - Zhou Minlu; Chen Jin; Yang Hongsheng; Yu Ye; Shan Rongrong; Cui Lei; Chu Chengmei; Hu Yang (结直肠肛门外科)
[Objectives] To investigate the effectiveness of teach-back health education combined with Photo Therapy in colorectal cancer patients with permanent enterostomy. [Methods] A retrospective analysis was conducted on the clinical data of 55 patients with colorectal cancer who underwent permanent enterostomy in our hospital between February 2022 and June 2023 and completed effective follow-up. During hospitalization and up to 12 weeks post-surgery, patients received staged teach-back health education on stoma care and staged Photo Therapy. The incidence of stoma-related complications within 12 weeks post-surgery was recorded. Comparisons of patients’ stigma of the disease, assessed by the Social Impact Scale (SIS), and quality of life, assessed by the Stoma-Quality of Life (SQOL) scale, were made at discharge and 13 weeks post-surgery. [Results] The incidence of stoma-related complications within 12 weeks post-surgery is 9.1% (5/55). At 13 weeks post-surgery, the scores of each dimension and the total score of SIS significantly decreased compared to those at discharge (P<0.05). Meanwhile, the scores of each dimension and the total score of the SQOL scale significantly increased compared to those at discharge (P<0.05). [Conclusion] Combining teach-back health education with Photo Therapy can help colorectal cancer patients with permanent enterostomy achieve better nursing effectiveness of stoma care, reduce the stigma of the disease, and improve their quality of life.